Quantification of active mitochondrial permeability transition pores using GNX-4975 inhibitor titrations provides insights into molecular identity - Richardson, Andrew P. (Biochem J, 2016)
Inhibition of the mitochondrial permeability transition pore (MPTP) by the novel inhibitor GNX-4975 was characterized. Titration of MPTP activity in de-energized rat liver mitochondria allowed determination of the number of GNX-4975-binding sites and their dissociation constant (K(i)). Binding sites increased in number when MPTP opening was activated by increasing [Ca(2+)], phenylarsine oxide (PAO) or KSCN, and decreased when MPTP opening was inhibited with bongkrekic acid (BKA) or ADP. Values ranged between 9 and 50 pmol/mg of mitochondrial protein, but the K(i) remained unchanged at ∼1.8 nM when the inhibitor was added before Ca(2+). However, when GNX-4975 was added after Ca(2+) it was much less potent with a K(i) of ∼140 nM. These data imply that a protein conformational change is required to form the MPTP complex and generate the GNX-4975-binding site. Occupation of the latter with GNX-4975 prevents the Ca(2+) binding that triggers pore opening. We also demonstrated that GNX-4975 stabilizes an interaction between the adenine nucleotide translocase (ANT), held in its ‘c’ conformation with carboxyatractyloside (CAT), and the phosphate carrier (PiC) bound to immobilized PAO. No components of the F(1)F(o)-ATP synthase bound significantly to immobilized PAO. Our data are consistent with our previous proposal that the MPTP may form at an interface between the PiC and ANT (or other similar mitochondrial carrier proteins) when they adopt novel conformations induced by factors that sensitize the MPTP to [Ca(2+)]. We propose that GNX-4975 binds to this interface preventing a calcium-triggered event that opens the interface into a pore.